Anemia and iron deficiency during pregnancy in rural Bangladesh - Hyder, S.M. Ziauddin; Persson, Lars-Ake; Chowdhury, AMR; Lonnerdal, B; Ekstrom, Eva-Charlotte (BRAC Research and Evaluation Division (RED), 2019)
Objective: To assess the prevalence of anemia, iron deficiency and iron deficiency anemia (IDA) among pregnant women in rural Bangladesh Design: Baseline data on 215 pregnant women who were invited to participate in an iron supplementation trial were used. The women were in their second trimester and selected at registration from 50 antenatal care centers. Hemoglobin (Hb) concentration of venous blood samples was measured by HemoCue® system. Serum was collected for \ . assessment of ferritin by imrnuno-radiometric assay and transferrin receptors (sTtR) by immunoassay double sandwich method. , Anemia was defined as having Hb concentration <110 giL, iron deficiency as serum ferritin <12 f.Lg/L and/or sTtR >8.5 mg/L and IDA as the combination of anemia and iron deficiency. High sTfR/serum ferritin ration was >500. Setting: The central part of Bangladesh, in a rural area of Mymensingh district between May-November, 1997. Results: Mean (SD) of Hb was 110 giL (14 giL), while median serum ferritin, sTfR and sTfRJserum ferritin was 13.7 f.Lg/L, 6.2 mg!L and 458, respectively. The prevalence of anemia was 50%, iron deficiency 54% and high sTfR/serum ferritin 48%. None of the study women had severe anemia. The ·prevalence of IDA was 33%. Of the anemic women 66% had iron deficiency and 64% high sTfR/serum ferritin. Conclusion: Both anemia and iron deficiency were highly prevalent. About two-thirds of the anemia cases were associated with iron deficiency. Sponsorship: The study was financially supported by Sida/SAREC, Sweden and BRAC, Bangladesh. Descriptors: Anemia, iron deficiency, iron deficiency anemia, serum transferrin receptor, serum ferritin, pregnant women, Bangladesh